Modification of PES membrane by PEG-coated cobalt doped iron oxide for improved Cu(II) removal - Chan, Kian Hwa (2015)
Modification of membranes using nanoparticles is another latest trend in membrane technology. In this work, the hydrophobic cobalt(II) doped iron oxide nanoparticles were coated with polyethylene glycol of molecular weight 600 so as to prevent their agglomeration thus improving their dispersion when added into the dope solution containing 20 wt% of polyethersulfone in dimethylformamide. The nanomodified membranes were characterized in terms of flux permeation (Q), wetting ability, contact angle, pore size and solute rejection. These membranes were then used to remove Cu(II) and its separation efficiency was found to improve significantly.